Pengaruh Price Earning Ratio, Leverage, dan Profitabilitas terhadap nilai perusahaan Food & Beverages yang terdaftar di Bursa Efek Indonesia Periode 2012-2015 - Aprillia, Riska, Sri Murwanti,SE.,MM (2017)
This study aimed to determine the effect of the price earnings ratio, leverage, and profitability of the company's value. To obtain data on these variables, taken from the financial statements of food and beverage companies listed in Indonesia Stock Exchange from 2012 - 2015. The data used is secondary data. Mechanical sampling using purposive sampling of 19 food and beverage companies listing on the Indonesia Stock Exchange acquired 15 companies that match the criteria. The method used in this research is multiple linear regression. Hypothesis test (t test and F) and the coefficient of determination). From this research, the price earnings ratio, leverage and profitability has a significant effect on the value of the company. In the F test showed that together - at a variable price earnings ratio, leverage and profitability significant effect on the value of the company.